USING CASE BASED LEARNING TO FOSTER CRITICAL LEARNING IN MEDICAL BIOCHEMISTRY - MALIK , FA; FAROOQ, B; KHAN , MA; QURESHI , ZH; AYUB , MT; SAHU , EH; BUKHARI , HSMS; RAZA , T (Biological and Clinical Sciences Research Journal, 2023)
The interventional study was conducted in the Department of Biochemistry, Nishtar Medical Hospital, from January 2021 to January 2022 to analyze the impact of case-based learning on first-year biochemistry students’ critical thinking skills and creative abilities. The study was conducted on 1st year MBBS students who had undergone CBL. A total of 60 students were included in the study. Study participants were randomly divided into a study group (n=30) and a control group (n=30). Pre-test questionnaires were administered to both groups; the control group was then seated in a separate room, and the study group was randomly subdivided into subgroups I, II, and III. Sub-groups were asked to design study cases on given topics and discuss the designed case with each other. The control group was asked to study the same topics individually. All participants then underwent a post-test. Responses were recorded. Results showed that the pre-test score (out of 20) in the study group ranged from 8.5-16.5 and in the control group from 9-17, which means that there was no significant difference between both groups before intervention (P>0.05). Post-test scores in the control group ranged from 8-17 and in the study group from 12-19, and this difference between the scores was statistically significant. Results showed that case-based learning increases students’ critical thinking skills and enables them to consider alternatives, imagine possibilities, and seek solutions.